PARENTING BERBASIS FITRAH DI ERA DIGITAL PADA PONDOK PESANTREN HIDAYATUL HASANAH DESA BANJAREJO KECAMATAN PANEKAN KABUPATEN MAGETAN - Christanti, Yana Dwi; Abdullah, La Ode; Sugiharto; Hartono, Halleina Rejeki Putri; Kurniawan, Yopie Diondy; Febrianti, Niken (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
This study aims to solve the problems experienced by partners related to anxiety about the bad influence of the digital era on child development. The method of implementation and the stages to be carried out by carrying out training on the preparation of simple financial statements. The process of organizing the training is carried out in several stages, namely the preparation, implementation and reporting stages. The findings reveal that the challenges of children in the digital era are also felt by teachers and parents at the Hidayatul Hasanah Islamic Boarding School in Banjarejo Village, Panean District, Madiun Regency because Islamic education is optimal, but in terms of digital supervision at home it is still not optimal, easy access to technology and the lack of knowledge and parental supervision of digitalization creates unrest among parents. Whereas supervision of the use of technology in children is very important because it will have an impact on the future of the child itself.